2022
DOI: 10.1021/acsorginorgau.1c00027
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Applications of Aryl Trifluoromethyl Diazoalkanes and Diazirines in Synthetic Transformations

Abstract: Aryl trifluoromethyl diazoalkanes and diazirines have become unique as reactants in synthetic methodology. As privileged compounds containing CF 3 groups and ease of synthetic access, aryl trifluoromethyl diazoalkanes and diazirines have been highlighted for their versatility in applications toward a wide range of synthetic transformations. This Perspective highlights the synthetic applications of these reactants as precursors of stabilized metal carbenes, i.e., donor−acceptor-substituted ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 86 publications
0
15
1
Order By: Relevance
“…7 When activated with heat or light, the diazirine group loses an equivalent of nitrogen gas to liberate a reactive carbene that can undergo rapid insertion into nearby C–H, O–H, or N–H bonds. 5,8 Shortly after our report in 2019 of a rationally designed bis-diazirine reagent ( 1 ) for crosslinking polyethylene, polypropylene, and other aliphatic polymers 9,10 the use of bis- and tetrakis-diazirines in materials science experienced an explosion of interest (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…7 When activated with heat or light, the diazirine group loses an equivalent of nitrogen gas to liberate a reactive carbene that can undergo rapid insertion into nearby C–H, O–H, or N–H bonds. 5,8 Shortly after our report in 2019 of a rationally designed bis-diazirine reagent ( 1 ) for crosslinking polyethylene, polypropylene, and other aliphatic polymers 9,10 the use of bis- and tetrakis-diazirines in materials science experienced an explosion of interest (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Diazirines are considered relevant chemical scaffolds usually employed as photo-labeling agents [ 11 ]. Their high stability—mainly the aryl-based diazirines—makes them appropriate for such a purpose, and to date several applications of diazirine-based compounds in organic synthesis and medicinal chemistry have been found [ 12 , 13 ]. West et al described the reactivity of the trifluoromethyl diazirine scaffold with amino acid side chains, in order to evaluate the labeling preferences of diazirines for peptidic biomolecules [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to heat or light, the strained diazirine heterocycle loses a molecule of nitrogen gas (N 2 ) to generate a highly reactive carbene, which in turn can insert into neighboring C−H bonds [15] . Thus, the use of bis ‐, tetrakis ‐, or poly ‐diazirines provides a convenient and practical method to rationally install molecular crosslinks into commercial polyolefins without the risk of competing fragmentation reactions, and without any requirement for functional groups to be already present along the polymer chain [13b, 16] . Recent structure‐function studies revealed that trifluoromethyl aryl diazirines bearing electron‐rich aryl groups were much more efficient at undergoing C−H insertion than the corresponding electron‐neutral or electron‐poor systems [17a] .…”
Section: Introductionmentioning
confidence: 99%